Social Media Used In Language Learning: Benefits And Challenges - Awal Kurnia Putra Nasution (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2022)
The use of social media that is rampant today also impacts the increasing use of social media in language learning. Seeing this reality, it is necessary to research to find the benefits and challenges of using social media in language learning. The research method used in this article is in the form of library research. Sources of research data are articles from the Scopus database and Google Scholar. The study results show that using social media in language learning brings good and various benefits, such as Increasing reading, writing, and vocabulary mastery to increase students' motivation. The benefits of social media in language learning are fully discussed in the text. The challenges faced are: integrating learning with social media and giving assignments during learning. The results of this study indicate the increasing use of technology in learning. Therefore, this research provides an opportunity to develop the use of social media in language learning in the future.